Sosialisasi Manajemen Pemeliharaan Ayam Petelur sebagai Upaya Peningkatan Ketahanan Pangan Kelompok PKK Desa Midang Lombok Barat - I Gede Nano Septian; Muh. Aidil Fitryan Fadjar Suryadi; Ni Ketut Dewi Haryani (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The community service activity in the form of a socialization program on laying hen management was conducted for the PKK women’s group in Midang Village, West Lombok Regency. This activity aimed to improve the knowledge and skills of the community, especially housewives, regarding proper and sustainable laying hen management practices. The implementation method included lectures, discussions, and question-and-answer sessions related to housing management, feeding, sanitation, animal health, and egg production management. The activity was carried out interactively with active participation from the participants throughout the program. The results showed that the participants had a high level of enthusiasm toward developing small-scale laying hen farming businesses at the household level. The participants also demonstrated an increased understanding of the importance of proper management practices in improving chicken productivity and health. In addition, this activity motivated the community to utilize laying hen farming as an alternative source of family income and a provider of nutritious food for households. Therefore, this socialization program is expected to become an initial step toward the development of community-based poultry farming in Midang Village, West Lombok Regency.